THE IMPORTANCE OF USING SOCIAL NETWORKING SITES IN TOURISM PROMOTION BY TOURISM AGENCIES - Bouguebrine Moufida; Benchenna Abdelali; Redjal Omar; Meddour Oualid (International Journal of Innovative Technologies in Social Science, 2024)
New technologies are fundamentally changing the way tourism agencies communicate, and as a result, these tourism agencies have to move from traditional to digital communications, using digital tools at the same time: websites, social networks, emails, etc. The study aimed to discuss the importance of social networking sites in tourism promotion by tourism agencies, through a questionnaire conducted on a sample of 40 tourism agencies. Through it, we have concluded that social networking sites are one of the most important methods that work to develop the tourism sector, and a basic basis through which the strategic position of the tourism agency can be improved. It is an important new element in promotion as a marketing lever to increase its reputation and improve its commercial performance by using a promotional strategy for its tourism offers and services through these networks. It also plays the role of a marketing channel and communication tool between the tourism agency and customers to meet their needs and desires.